EFFECT OF EXERCISE ON PHYSICAL STATUS OF PRIMIPARUS WOMEN AT PUERPERAL STAGE - Nikpoor, S; Barazandeh, G; Taavooni, S; Haghani, H (Iran University of Medical Sciences, 2001)
Background: Women are recommended to do appropriate exercise after delivery as soon as possible. The main purpose of these practices is to restore physical status of mothers.   Objective: To determine the effects of puerperal exercise on physical status of primiparus women .   Design: This was a randomized clinical trial study with control group. The evaluation of physical status of women in this study were based on weight, waist, abdominal- gluteal ratio, flexibility of waist and hamstring muscle strength of abdominal and pelvic floor muscles. These parameters were determined 10-15 days and 3 mouths after delivery by the means of specific tests and scales. Subjects in the case group practiced postpartum exercises but subjects who were in control group did not. In order to assess the efficacy of the postpartum exercise, the mentioned variables were compared between two groups (case and control) .   Samples: Through a consecutive sampling, eighty women in postpartum stage were selected.   Results: The mean value of weight and waist measurement in the case group showed a significant decrease and flexibility of waist and hamstring muscles and abdominal muscles strength showed an increase comparing with the control group (PV= 0.000). However there was no significant difference between case and control groups regarding abdominal- gluteal ratio and pelvic floor muscle strength.   Conclusion: Based on the findings of this study, performance of postpartum exercise diminished weight and waist measurement and increased abdominal muscles strength and flexibility of waist and hamstring muscle in puerperal women. Therefore, it is recommended to try to enhance the knowledge and practice of women about the postpartum exercise. In the meantime, the same study can be recommended for multiparus women.